Aspects of supersymmetric phenomenology - Harrison, P (1984)
﻿ The current state of supersymmetric models of elementary particle physics is reviewed. Full calculations of the differential cross sections for the production of squarks and gluinos are performed, and the results folded with parton distributions to give total cross sections for pp and pp processes. The gluino production rate is used together with an analysis of its decay, taking proper account of the transverse momentum distribution of the decay products, to derive limits on the gluino mass from existing beam dump experiments; this limit is rather weak, typically mg > 3 GeV (the exact results depend on the details of the supersymmetric model). The production of squarks and sleptons in ep processes is considered, allowing for gaugino-Higgsino mixing, and the prospects for using these processes to extract information about the gaugino-Higgsino mixing parameters are discussed. Finally we consider the production of squarks or sleptons in association with a photino; although of order of ϰ3 in perturbation theory, this process has a characteristic signature and may be where squarks or sleptons are first discovered if they are too heavy to be pair produced at LEP.